Iceland : Ex Post Evaluation of Exceptional Access Under the 2008 Stand-by Arrangement. (IMF Staff Country Reports; Country Report ;, 2012)
The ex-post evaluation of Iceland's Exceptional Access under the 2008 Stand-By Arrangement is presented. In the wake of the global financial crisis in late 2008, Iceland has experienced a deep financial and economic crisis of its own. Domestically, the rapid increase in lending fuelled bubbles in all asset classes, particularly the stock market and real estate. Inflated asset prices and nontransparent cross-financing and related party lending between banks and holding companies helped mask poor asset quality and facilitated the financing of credit expansion by borrowing abroad, increasing vulnerability.